PENGARUH TATA KELOLA PERUSAHAAN DAN FAKTOR-FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Kartina Natalylova; Angela Natalia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to obtain empirical evidence about the effect of institutional ownership, managerial ownership, board of commissioner meeting frequency, audit committee meeting frequency, firm size, leverage, profitability and free cash flow as independent variables on earnings management as dependent variable. The population of this research are non-financial firms that listed in Indonesia Stock Exchange (IDX) during the period of 2018 until 2020. The sample used in this study were 103 companies or 309 data. This study used a purposive sampling technique as a sample selection method and the data in this study were tested and analyzed using multiple regression method. Data processing was carried out using the SPSS 25 application. The results of this study show that profitability and free cash flow have an influence on earnings management. Meanwhile, other independent variables such as institutional ownership, managerial ownership, board of commissioner meeting frequency, audit committee meeting frequency, firm size and leverage have no influence on earnings management